Bangsa Indonesia di Tengah Fenomena Kekerasan dan Ketidakadilan (Perspektif Filsafat Pancasila) - Robby Habiba Abror (UIN Sunan Kalijaga Yogyakarta, 2012)
Pancasila serves as the state philosophy, way of life, and national ideology in Indonesia. Once the Pancasila as the nation ideology is functionally applied, the balanced life of the nation is present. In reality, Pancasila is abused and politized in a destructive interest to justify immoral actions. This affected to the people misery, as found in Lapindo case in Sidoarjo and most Indonesian workers abroad. In this scene, Pancasila should be redefined pointing the critical-philosophical mode of reflection. This could be stimulated to gain creative-historical potency constructing Indonesia better.